Pulse generation scheme for flying electromagnetic doughnuts - Papasimakis, Nikitas (2018)
Transverse electromagnetic plane waves are fundamental solutions of Maxwells equations. It is less known that a radically different type of solutions has been described theoretically, but has never been realized experimentally, that exist only in the form of short bursts of electromagnetic energy propagating in free space at the speed of light. They are distinguished from transverse waves by a doughnutlike configuration of electric and magnetic fields with a strong field component along the propagation direction. Here, we demonstrate numerically that such flying doughnuts can be generated from conventional pulses using a singular metamaterial converter designed to manipulate both the spatial and spectral structure of the input pulse. The ability to generate flying doughnuts is of fundamental interest, as they shall interact with matter in unique ways, including nontrivial field transformations upon reflection from interfaces and the excitation of toroidal response and anapole modes in matter, hence offering opportunities for telecommunications, sensing, and spectroscopy.